Isolated sleep paralysis - Sawant, Neena S. (Medknow Publications, 2005)
Sleep paralysis (SP) is a cardinal symptom of narcolepsy. However, little is available in the literature about isolated sleep paralysis. This report discusses the case of a patient with isolated sleep paralysis who progressed from mild to severe SP over 8 years. He also restarted drinking alcohol to be able to fall asleep and allay his anxiety symptoms. The patient was taught relaxation techniques and he showed complete remission of the symptoms of SP on follow up after 8 months.